2004
DOI: 10.1152/jn.00696.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Beauty

Abstract: We have used the technique of functional MRI to address the question of whether there are brain areas that are specifically engaged when subjects view paintings that they consider to be beautiful, regardless of the category of painting (that is whether it is a portrait, a landscape, a still life, or an abstract composition). Prior to scanning, each subject viewed a large number of paintings and classified them into beautiful, neutral, or ugly. They then viewed the same paintings in the scanner. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
577
4
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(633 citation statements)
references
References 32 publications
40
577
4
12
Order By: Relevance
“…For example, Cela-Conde et al (2004) found that liked pictures elicited stronger prefrontal cortex activations than disliked pictures. Kawabata and Zeki (2004) found stronger activation of orbitofrontal cortex for pictures found beautiful than for pictures judged ugly, and stronger activation of sensorimotor cortex for the opposite contrast. Calvo-Merino et al (2008) applied this approach to dance actions.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, Cela-Conde et al (2004) found that liked pictures elicited stronger prefrontal cortex activations than disliked pictures. Kawabata and Zeki (2004) found stronger activation of orbitofrontal cortex for pictures found beautiful than for pictures judged ugly, and stronger activation of sensorimotor cortex for the opposite contrast. Calvo-Merino et al (2008) applied this approach to dance actions.…”
Section: Introductionmentioning
confidence: 80%
“…The few published neuroaesthetic studies using visual stimuli have not achieved consensus on the lateralisation of aesthetic responses. For example, two fMRI studies report left sensorimotor cortex activations associated with explicit subjective judgements of ugliness (Di Dio et al, 2007;Kawabata and Zeki, 2004). In contrast, Calvo-Merino et al's (2008) participants first viewed dance movements, and later gave them aesthetic evaluations in a separate session.…”
Section: Hemispheric Lateralisation Of Aesthetic Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Concrete, or representational, pictures are preferred to abstract ones (e.g. Kawabata & Zeki, 2004;Vartanian & Goel, 2004); the visual complexity of pictures, websites and graphic patterns has a significant influence on aesthetic appeal judgements (e.g. Berlyne, 1974;Bauerly & Liu, 2008;Jacobsen & Hofel, 2002;Lai et al, 2010;Moshagen & Theilsch, 2010Orth & Wirtz, 2014); and, of course, familiarity enhances appeal for a wide range of…”
Section: Stimulus Characteristics That Might Affect Icon Appeal Evalumentioning
confidence: 99%
“…Brain imaging research on neuroesthetic shows that the core neural networks underlying pleasure evoked by beauty are likely to engage the same neural structures that mediate emotions, and, in particular, the reward systems (Cela-Conde et al, 2004;Ishizu and Zeki, 2011;Kawabata and Zeki, 2004;Marzi and Viggiano, 2010;Vartanian and Goel, 2004;Wiesmann and Ishiai, 2008;Chatterjee et al, 2009). Thus, it has been found that the esthetic experience involves a widely distributed circuit with greater activation for beautiful stimuli in anterior cingulate gyrus, dorsolateral and medial frontal cortices (Berridge and Kringelbach, 2008;Breiter et al, 2001;Di Dio et al, 2011;Kirk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%